Perancangan Baru Interior Gereja-mal/ruko Jb3 Church Home For All Di Kota Bandung Dengan Pendekatan Religius Karismatik - Sean Purnama, Pascal; Nur Arief Hapsoro, Agustinus; Aulia Widyaevan, Dea (eProceedings of Art & Design, 2024)
: In Indonesia, Christians as a minority group face limitations in developing church buildings. This has prompted the Christian community in urban Indonesia to develop a special typology that combines churches with malls or shophouses. Crane (2021) suggests that churches of this type have the potential to become multi-purpose spaces, such as, Businesses on Mondays to Fridays, small groups in the evenings, worshiping God on weekends. The diverse utilization of space based on function becomes important to discuss for the sustainability of the church as a community center. In addition to its spatial function, the church must also be able to give meaning and identity to its space. As Widyakusuma (n.d.) states, "Users define and give meaning to space, space also defines and gives meaning to users." The results of surveys and interviews showed several problems with JB3 Church Home For All, such as, circulation, acoustics, layout. Moreover, considering the new typology of church-mall/shophouses mentioned by Crane (2021), churches of this type experience confusion in defining their sacredness as the identity of a church building. Based on the problems mentioned above, a new design is needed for JB3 Church Home For All. Keywords: church, interior, religious, sacred, shophouses